Evaluation of Antimicrobial Susceptibility of Gram Negative Organisms by Minimum Inhibitory Concentration Method in Bandar Abbas, South of Iran - Mahin Jamshidi Makiani; Maryam Farasatinasab; Somayyeh Nasiripour (Research Center for Rational Use of Drugs (RCRUD), 2017)
Background: Antibiotic-resistant pathogens are problem in many geographic areas. The emergence of antimicrobial drug resistant organisms needs special attention. Methods: In a cross sectional prospective study during one year clinical samples were cultured and evaluated in general hospital, south of Iran. Samples were cultured and Organisms were identified by microbiologic methods. Minimum Inhibitory Concentration for seven antibiotics were evaluated. Results:  In this study 494 positive samples were evaluated. The most common site of isolation was urinary system. The most common isolated organisms were E.coli, Kelebsiela pneumonia and Pseudomona aeroginosa. Resistance to ceftrixone, ceftazidime and cefepime was more than %50. Conclusions: Resistance to ceftrixone, ceftazidime and cefepime was high in our study.